An Application of Geoinformatics Technology to Assess Green Space Potential for Urban Resilience Samut Sakhon Province - Janchidfa, Kannika; Patnukao, Areerut (Journal of Letters, 2024)
Rapid urbanization in Samut Sakhon province is transforming urban green spaces and public spaces, creating an urgent need to strengthen capacity to improve essential urban ecosystems and to create a sustainable future for everyone. The objective of this research is to assess the potential of suitable green spaces for urban resilience in Samut Sakhon province by applying geographic information system (GIS) tools and multicriteria analysis using an analytical hierarchy process (AHP), together with interviews. There are four main criteria used in the data analysis: (1) socioeconomic factors, (2) physical factors, (3) natural and environmental factors, and (4) access to infrastructure. In addition, there are ten subcriteria: (1) current land use, (2) population density, (3) distance from pollution source, (4) land ownership, (5) distance from water area, (6) size of green area per population, (7) distance from disaster area (flood), (8) distance from biodiversity sites, (9) distance from park, and (10) distance to facilities. The result of the potential assessment of green areas that are appropriate for urban resilience showed that besides 26.72 percent of the urban area, 73.28 percent of the province consists of potential areas, which can be classified into five levels based on the potential of the area to support urban expansion, comprising very high potential (3.86 percent), high potential (61.48 percent), medium potential (34.13 percent), low potential (0.49 percent), and very low potential (0.05 percent). Most of the potential areas of each subdistrict are diverse in type of land use, including areas for aquaculture, fruit trees, orchards, and natural water sources, along with low-lying areas, mangrove forests, and rice fields. These areas are spread across various subdistricts near urban and industrial areas in the province. This is because these areas need green spaces to support urban expansion in order to promote sustainability and provide increased flexibility.